Comparing Agile Leadership and Transformational Leadership: A Literature Review on Leadership Effectiveness - David David; Laura Lahindah; Muhammad Eka; Sih Ramping Usadani; Susanti Setiawaty; Deri Ramadhan (PT. Anagata Sembagi Education, 2025)
In an increasingly complex business world, leadership plays a key role in determining organizational effectiveness. Agile Leadership and Transformational Leadership are two leadership approaches that have unique characteristics in managing change and achieving business goals. Agile Leadership emphasizes flexibility, rapid adaptation, and decentralized decision-making, making it suitable for dynamic environments such as the technology and startup industries. Meanwhile, Transformational Leadership is oriented towards long-term vision and gradual organizational cultural change with leaders as the main inspirators. Both approaches have their own advantages, but also face challenges in their implementation, such as cultural resistance in Agile Leadership and dependence on charismatic leaders in Transformational Leadership. This study uses a literature study method to compare the effectiveness of the two leadership models in various organizational contexts. The results of the analysis show that the combination of Agile Leadership and Transformational Leadership can create a balance between organizational agility and long-term stability. By understanding the advantages and limitations of each model, organizations can implement a more adaptive and innovation-oriented leadership strategy to face increasingly dynamic market changes.